Comparison of porosity models for fluidized beds - Flamarz, Sherko Ahmed (Kurdistan Journal of Applied Research, 2017)
The paper describes a comparison between four numerical models of porosity, for better understanding the influence of porosity on the hydrodynamics (macroscopic and microscopic) behaviors of fluidized beds. The study has been done through an approach based on combine discrete-continuum to achieve the simulations. This approach deals with the modeling of the interactions between the fluid-solid. In which the discrete approach is used for localizing the position and velocity of each individual particles based on Newton’s 2nd law of motion, using a numerical time stepping scheme. While the continuum approach is based on finite volume method, which is solved the fluid flow equations (Navier-Stokes equations). The geometry of fluidizing column was; column diameter (D=0.096 m) and column height (H=1 m). Glass grains were firstly deposited inside the column, and then subjected to the range of inlet water velocity (0-0.14 m.s-1). The results of simulations are point out those four models of porosity, achieved comparable results for simulating fluidized beds. The simulations results were compared and showed a good agreement and consistency with the experimental data in the literatures. In other hand, the simulations results revealed that the models of porosity, which based on the microscopic scale, are most reliable between the models of porosity. However the differences between these models must be analyzed and kept in mind in order to select the appropriate porosity model. The results revealed that the porosity is an important parameter which effect on the hydrodynamics behavior of fluidized beds during the fluidization processes.